Eco Traditional Bamboo-Based Agroforestry and Its Services for Privately Owned Forest Cover and Sustainability - Hani, Aditya; Suryanto, Priyono; Murniati, Murniati; Widiyatno, Widiyatno (AGRIVITA Journal of Agricultural Science, 2024)
This study aims to determine bamboo agroforestry system in maintaining sustainability of privately owned forest and contribution of bamboo community forests to the farmers' economy. Research on the composition of privately owned forest species was carried out using a survey method. There were 37 observation plots evenly distributed in the study location villages. Land cover image data obtained from Sentinel-2 Imagery were compared based on land-cover classification. Thirty respondents were interviewed to obtain social and economic data. Data related to the pattern and composition of species diversity of privately owned forest were displayed in an ordinal space and processed by employing Non-metric Multi-Dimensional Scaling analysis. Data from interviews were analyzed using descriptive methods which were presented in the form of tables and graphs. Results showed that privately owned forest were able to increase tree vegetation cover in Ciamis Regency by 3.367%. The bamboo privately owned forest was composed of wood and bamboo, fruit plants, plantation crops, horticulture, and food plants. Privately owned forest contribute 24.49% to farmers' income with coffee as the main commodity. Bamboo has contributed 15.42% of the income from privately owned forest. Farmers will keep maintaining bamboo trees because they have provided economic, social, and environmental benefits.